Serodiagnosis of Helicobacter pylori: comparison of enzyme-linked immunosorbent assays. - Talley, N J (1991)
Enzyme-linked immunosorbent assays (ELISAs) have been developed to diagnose Helicobacter pylori infection. However, the methods are not standardized. We therefore prospectively evaluated the sensitivities and specificities of ELISAs developed in the United States and the United Kingdom in a study population comprising 41 consecutive symptomatic outpatients and 35 volunteers. At endoscopy, multiple biopsies were obtained for histology and culture and stained sections were graded for chronic gastritis, active chronic gastritis, and density of H. pylori. Serum samples were analyzed for H. pylori by ELISA. The first set of assays for immunoglobulin G (IgG) and IgA used a pool of sonicated isolates of H. pylori from five patients in the United States (antigen A). The second set of assays, developed in the United Kingdom, used three different antigens: antigen 1, an acid-extractable surface antigen; antigen 2, an acid-extractable antigen from an aflagellate variant; and antigen 3, a urease-containing fraction. Cutoff scores for positive results were determined a priori on the basis of previous serological studies. There was close agreement between histology and culture. In the study population, 36% of the individuals were H. pylori positive. The diagnostic value of the different ELISAs were highly comparable, and the crude antigens performed as well as the more purified antigens. The antigen A IgG had a sensitivity and specificity of 96 and 94%, respectively; the values for antigen 1 were 93 and 96%, respectively. The antigen A IgA and antigen 3 assays were the least sensitive tests.(ABSTRACT TRUNCATED AT 250 WORDS)